Kahoot-Based Classroom Action Research on Nahwu Learning Interest: Penelitian Tindakan Kelas Berbasis Kahoot tentang Minat Belajar Nahwu - Salman Al Farisi; Najih Anwar (Universitas Muhammadiyah Sidoarjo, 2025)
This study examines the integration of digital learning media in Arabic grammar instruction at the junior secondary level. General Background: The digital era and Industrial Revolution 4.0 require teachers to adopt innovative technology-based media to create engaging and student-centered learning environments. Specific Background: Nahwu, as a fundamental component of Arabic grammar, is often perceived as difficult and less appealing by students, resulting in low learning interest. Knowledge Gap: Although Kahoot has been applied in various Arabic language skills, limited studies focus specifically on its application in Nahwu learning interest at the junior secondary level. Aims: This classroom action research aims to increase Grade IX students’ interest in learning Nahwu at SMP Muhammadiyah 8 Tanggulangin Sidoarjo through Kahoot-based instruction. Results: The findings indicate a progressive increase in learning interest from 41% in the pre-cycle to 62% in Cycle I and 82% in Cycle II, categorized as strong. Improvements were observed across four indicators: enjoyment, attraction, attention, and involvement. Novelty: The study specifically applies Kahoot to Nahwu instruction within a structured classroom action research design. Implications: Kahoot-based learning supports active participation, competitive engagement, and structured grammar instruction in Arabic language classrooms. Keywords: Kahoot, Nahwu, Classroom Action Research, Arabic Grammar Learning, Learning Interest Key Findings Highlights: Student motivation indicators improved consistently across two action cycles. Interactive quiz sessions increased classroom participation and engagement. Grammar instruction became more structured through technology-supported activities.